Plasma biomarkers for the identification of women at risk for early-onset preeclampsia. (4th March 2017) - Kolialexi, Aggeliki; Tsangaris, George Th; Sifakis, Stavros; Gourgiotis, Dimitris; Katsafadou, Aggeliki; Lykoudi, Alexandra; Marmarinos, Antonios; Mavreli, Danai; Pergialiotis, Vassilis; Fexi, Dimitra; Mavrou, Ariadni; Papaioanou, George K.; et al.
ABSTRACT: Background : To identify potential biomarkers in the 1st trimester of pregnancy for the identification of women destined to develop early onset preeclampsia (EOPE). Methods: Blood samples were obtained from pregnant women at 11–13 weeks of gestation. Women were followed up until delivery. Five samples from EOPE complicated pregnancies and 5 from unaffected ones were analysed using 2-DE and MALDI-TOF-TOF MS/MS. The altered expression of selected proteins was verified by ELISA in an extended sample cohort. Results : Twelve proteins were differentially expressed in the plasma of women who subsequently developed EOPE as compared to controls. Alpha-1-antitrypsin (A1AT), CD5 antigen-like molecule (CD5L) Keratin, type I cytoskeletal 9 (K1C9), Myeloid cell nuclear differentiation antigen (MNDA), Transferrin (TRFE) and Vitamin D-binding protein (VTDB) were up-regulated with fold changes 3.14, 2.18, 1.53, 1.53, 4.26 3.38 respectively, whereas Alpha-2-HS-glycoprotein (FETUA), Beta-2-glycoprotein 1 (APOH), Complement factor B (CFAB), Haptoglobin (HPT), Vitronectin (VTNC) and Zinc-alpha-2-glycoprotein (ZA2G) were down-regulated with fold changes -0.38, -0.76, -0.24, -0.47, -0.23, and -0.50 respectively. The down-regulation of APOH, VTNC and HPT was verified using ELISA. Conclusions : The differentially expressed proteins represent potential biomarkers for the early screening for EOPE. Follow-up experiments however are necessary for evaluation.